Isolation and identification of patient-derived liver cancer stem cells and development of personalized treatment strategies - Tingting Guo; Shuai Zhang; Weiping Zeng; Yan Liang; Jinghe Xie; ShouPei Liu; Yaqi Qiu; Yingjie Fu; Yimeng Ou; Keqiang Ma; Bailin Wang; Weili Gu; et al. (Journal of Translational Medicine)
Abstract Background Liver cancer stem cells (LCSCs) are thought to drive the metastasis and recurrence, however, the heterogeneity of molecular markers of LCSCs has hindered the development of effective methods to isolate them. Methods This study introduced an effective approach to isolate and culture LCSCs from human primary liver cancer (HPLC), leveraging mouse embryonic fibroblasts (MEFs) as feeder cells in conjunction with using defined medium. Isolated LCSCs were further characterized by multiple approaches. Transcriptome sequencing data analysis was conducted to identify highly expressed genes in LCSCs and classify different subtypes of liver cancers. Results Total sixteen cell strains were directly isolated from 24 tissues of three types of HPLC without sorting, seven of which could be maintained long-term culture as colony growth on MEFs, which is unique characteristics of stem cells. Even 10 of cloned cells formed the tumors in immunodeficient mice, indicating that those cloned cells were tumorgenic. The histologies and gene expression pattern of human xenografts were very similar to those of HPLC where these cloned cells were isolated. Moreover, putative markers of LCSCs were further verified to all express in cloned cells, confirming that these cells were LCSCs. These cloned LCSCs could be cryopreserved, and still maintained the feature of colony growth on MEFs after the recovery. Compared to suspension culture as conventional approach to culture LCSCs, our approach much better maintained stemness of LCSCs for a long time. To date, these cloned cells could be cultured on MEFs over 12 passages. Moreover, bioinformatics analysis of sequencing data revealed the gene expression profiles in LCSCs, and liver cancers were classified into two subtypes C1 and C2 based on genes associated with the prognosis of LCSCs. Patients of the C2 subtype, which is closely related to the extracellular matrix, were found to be sensitive to treatments such as Cisplatin, Axitinib, JAK1 inhibitors, WNT-c59, Sorafenib, and RO-3306. Conclusion In summary, this effective approach offers new insights into the molecular landscape of human liver cancers, and the identification of the C2 subtype and its unique response to the treatment pave the way for the creation of more effective, personalized therapeutic strategies.